Composição e distribuição de coleoptera aquáticos (insecta) em córregos de baixa ordem no Estado de São Paulo, Brasil - Segura, Melissa Ottoboni (Universidade Federal de São Carlos, 2007)
The beetles are an important part of the insect fauna of most aquatic ecosystems. However, with the exception of the Elmidae, they have not been used extensively for water quality evaluation. This is due in large part to the fact that most water beetle adults and larvae, with the exception of the elmids, some adult Dryopidae and larvae Psephenidae, are air-breather and do not depend on dissolved oxygen in water for respiration. However, many beetles appear to live and reproduce in restricted aquatic habitats, thus can colonize the smallest water bodies, and the loss of those habitats may mean a loss of those species. And, if a high diversity of species is indicative of good water quality, then the high diversity of beetles in an aquatic environment is certain important. The main goals of this study were to evaluate and to compare the impact on the beetle fauna from small streams in reference (Conservation Areas), sugar-cane agriculture and Eucalyptus plantations and pasture areas. The main question addresses here was: which are the main consequences for diversity and abundance of beetles with deforestation of riparian vegetation. In this study were visited six Conservation Areas where 20 streams were sampled and three landscape impacted areas by sugar-cane agriculture and Eucalyptus plantations and pasture, where 14 streams were studied. The results showed a high diversity of Coleoptera have been identified 49 genera, of which 44 genera were collected in reference areas and only 17 genera were registered in impacted areas. The family Elmidae comprised 83.47% of the 1506 specimens from conservation areas. However in the impacted areas the family Hydrophilidae was more abundant, it represented 34.8% of the 87 specimens collected in these locations. The results of physics an chemistry of the water variables did not show much differences between both situations (Conservation and impacted areas), however the deforestation of the riparian vegetation was a determinant factor in the alteration of the composition, diversity and abundance of beetles in the studied streams.
Keywords: Insetos aquáticos; Fatores abióticos; Unidades de conservação; Monocultura; Região neotropical; CIENCIAS BIOLOGICAS::ECOLOGIA